Daily television exposure, parent conversation during shared television viewing and socioeconomic status: Associations with curiosity at kindergarten. - Prachi E Shah (Public Library of Science (PLoS), 2021)
Objective To examine the main and interactive effects of the amount of daily television exposure and frequency of parent conversation during shared television viewing on parent ratings of curiosity at kindergarten, and to test for moderation by socioeconomic status (SES). Study design Sample included 5100 children from the Early Childhood Longitudinal Study, Birth Cohort. Hours of daily television exposure and frequency of parent screen-time conversation were assessed from a parent interview at preschool, and the outcome of early childhood curiosity was derived from a child behavior questionnaire at kindergarten. Multivariate linear regression examined the main and interactive effects of television exposure and parent screen-time conversation on kindergarten curiosity and tested for moderation by SES. Results In adjusted models, greater number of hours of daily television viewing at preschool was associated with lower curiosity at kindergarten (B = -0.14, p = .008). More frequent parent conversation during shared screen-time was associated with higher parent-reported curiosity at kindergarten with evidence of moderation by SES. The magnitude of association between frequency of parent conversation during television viewing and curiosity was greater for children from low SES environments, compared to children from high SES environments: (SES ≤ median): B = 0.29, p < .001; (SES > median): B = 0.11, p < .001. Conclusions Higher curiosity at kindergarten was associated with greater frequency of parent conversation during shared television viewing, with a greater magnitude of association in low-SES families. While the study could not include measures of television program content, digital media use and non-screen time conversation, our results suggest the importance of parent conversation to promote early childhood curiosity, especially for children with socioeconomic disadvantage.